Effectiveness of Bacillus clausii (O/C, N/R, SIN, T) in the Prevention of Antibiotic-Associated Diarrhea and Gastrointestinal Symptoms: A Systematic Review - Ana Teresa Abreu; Rodrigo Vázquez Frías; Christian Boggio Marzet; Juan Pablo Stefanolo; Alejandro Concha Mejía; Luis Bustos Fernández; Oscar Laudanno; Dimas Rosa; Maria Claudia Cruz Serrano; Karen Cárdenas; Julio Zuluaga (Antibiotics)
Background: Dysbiosis and antibiotic-associated diarrhea (AAD) are significant concerns in clinical settings. Probiotics, such as Bacillus clausii (O/C, N/R, SIN, T), a spore-forming bacterium resistant to gastrointestinal conditions and most commonly used antibiotics, emerge as a promising approach. We aim to assess the role of B. clausii in preventing AAD in children and adults during antibiotic therapy. Materials and methods: A systematic literature search was conducted across multiple databases, including MEDLINE, EMBASE, Cochrane Library, LILACS, and SciELO, up to May 2024. Studies were included if they involved B. clausii (O/C, N/R, SIN, T) administration during antibiotic treatment and reported AAD-related outcomes. Results: A total of four studies were included in the review. The studies comprised two randomized controlled trials (RCTs), one meta-analysis of RCTs, and one expert consensus. The primary outcome was the effectiveness of B. clausii (O/C, N/R, SIN, T) in reducing the incidence of diarrhea. Results showed a significant reduction in the risk of AAD and gastrointestinal symptoms in patients receiving it at a dosage of 4 × 109 CFU/day for children and 6 × 109 CFU/day for adolescents and adults for up to 14 days. Conclusions: B. clausii (O/C, N/R, SIN, T) appears to be an effective probiotic for preventing AAD in adults and children. It significantly improves gastrointestinal symptoms associated with antibiotic treatment, including diarrhea, nausea, and epigastric pain. Future studies are recommended to further elucidate its effectiveness in diverse populations, especially in low- and middle-income countries.